2011
DOI: 10.7150/ijms.8.514
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Pulmonary Function is an Independent Risk Factor for Atrial Fibrillation: The Takahata Study

Abstract: Background: Chronic pulmonary disorders, such as chronic obstructive pulmonary disease (COPD) and fibrosing lung diseases, and atrial fibrillation (AF), are prevalent in elderly people. The impact of cardiac co-morbidities in the elderly, where pulmonary function is impaired, cannot be ignored as they influence mortality. The relationship between the prevalence of AF and pulmonary function is unclear. The aim of this study was to evaluate this relationship in participants in a health check. Methods: Subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 35 publications
(48 reference statements)
2
52
0
6
Order By: Relevance
“…This study was part of the Molecular Epidemiological Study of the Regional Characteristics of 21st Century Centers of Excellence (COE) Program and the Global Centers of Excellence Program in Japan 13-19. The Ethics Committee of Yamagata University School of Medicine approved the study, the study was conducted in accordance with the Declaration of Helsinki and all the participants gave written informed consent prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of the Molecular Epidemiological Study of the Regional Characteristics of 21st Century Centers of Excellence (COE) Program and the Global Centers of Excellence Program in Japan 13-19. The Ethics Committee of Yamagata University School of Medicine approved the study, the study was conducted in accordance with the Declaration of Helsinki and all the participants gave written informed consent prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…), что приводит к развитию сер-дечно-сосудистых заболеваний (АГ, ИБС, ХСН) и по-вышению риска сердечно-сосудистых событий в этой группе пациентов. При обсуждении механизмов влия-ния ХОБЛ на возникновение аритмий в литературе, как правило, описываются характеристики правых камер сердца, аритмогенные эффекты терапии [3,4,[7][8][9]. В на-шем исследовании выявлены ранее описанные в ли-тературе взаимосвязи морфо-функциональных пара-метров правых камер сердца с характеристиками тече-ния ХОБЛ.…”
Section: Discussionunclassified
“…Негативное влияние на сердечно-сосудистую систему таких меха-низмов, как системное воспаление, оксидативный стресс, эндотелиальная дисфункция, гипоксия у боль-ных ХОБЛ приводит к развитию артериальной гипер-тензии (АГ), ишемической болезни сердца (ИБС), хронической сердечной недостаточности (ХСН), арит-мий. По некоторым данным фибрилляция предсердий (ФП) чаще встречается среди больных ХОБЛ, чем в об-щей популяции, и связана с тяжестью бронхообструк-ции и проаритмогенными эффектами ингаляционной терапии ХОБЛ [3,4]. Наличие ФП у больных ХОБЛ не-гативно влияет на исходы, учитывая высокий риск тромбоэмболических осложнений и ремоделирование сердца с развитием сердечной недостаточности [5,6].…”
unclassified
“…The postulated mechanisms for arrhythmias in these patients include the presence of hypoxia, elevation of pulmonary pressures, the risk of coronary artery disease and the presence chronic inflammation (19,21). Hypoxia results in increased sympathetic activity thereby increasing the risk for arrhythmias.…”
Section: Drugs To Treat Ipf and Their Effects On The Heartmentioning
confidence: 99%
“…The side effect profile of Pirfenidone mainly included gastrointestinal side effects but no cardiac side effects were reported (30) and the same results were found in the CAPACITY trial, which was performed in 113 surgery difficult, increased age and the increased risk of coronary artery disease in patients with IPF. Shibata et al studied patients with IPF and COPD over 5 years to assess the causal relationship between pulmonary function tests and the development of AF (19). They reported that both decrease in FEV% (forced expiratory volume) (OR, 0.982; CI, 0.965 to 0.999; p < 0.05) and FVC% (functional vital capacity) (OR, 0.977; CI, 0.956 to 0.998; p < 0.05) were independent risk factors for development of AF.…”
Section: Drugs To Treat Ipf and Their Effects On The Heartmentioning
confidence: 99%